Answer:
x = 2, x = 3, x = 6, x = 1
Explanation:
1
2(x + 3) = 10 ( divide both sides by 2 )
x + 3 = 5 ( subtract 3 from both sides )
x = 2
2
2(x + 3) = 9 + x ← distribute parenthesis on left side
2x + 6 = 9 + x ( subtract x from both sides )
x + 6 = 9 ( subtract 6 from both sides )
x = 3
3
2(2x + 1) = 3x + 8 ← distribute parenthesis on left side
4x + 2 = 3x + 8 ( subtract 3x from both sides )
x + 2 = 8 ( subtract 2 from both sides )
x = 6
4
2(2x + 3) = x + 9 ← distribute parenthesis on left side
4x + 6 = x + 9 ( subtract x from both sides )
3x + 6 = 9 ( subtract 6 from both sides )
3x = 3 ( divide both sides by 3 )
x = 1